Iron(III) Pincer Complexes as a Strategy for Anticancer Studies. Issue 12 (16th February 2017) - Estrada‐Montaño, Aldo S.; Ryabov, Alexander D.; Gries, Alexandre; Gaiddon, Christian; Le Lagadec, Ronan
Abstract : [Fe(NCN)2 ]PF6 (1· PF6 ) [NCHN = 1, 3‐di(pyridin‐2‐yl)benzene] was readily obtained by a transmetalation reaction between [Fe3 (CO)12 ] and Hg(NCN)Cl followed by a metathesis reaction with KPF6 . X‐ray diffraction, electron paramagnetic resonance spectroscopy, and cyclic voltammetry studies confirmed the proposed structure. Cytotoxic assays in human colon cancer (HCT‐15), lung cancer (SKLU), and gastric cancer (AGS, KATOIII) cells were performed, and the IC 50 data obtained for all cell lines showed that1· PF6 has a much higher activity than cisplatin. Abstract : [Fe(NCN)2 ]PF6 [NCHN = 1, 3‐di(pyridin‐2‐yl)benzene] as a bis(pincer)iron(III) compound shows much higher cytotoxic activity than cisplatin against the HTC15, SKLU, AGS, and KATOIII cancer cell lines with IC 50 < 1 µm .